2015
DOI: 10.1002/jmv.24139
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus, adenoviruses, and mixed acute lower respiratory infections in children in a developing country

Abstract: There is growing evidence suggesting greater severity and worse outcomes in children with mixed as compared to single respiratory virus infections. However, studies that assess the risk factors that may predispose a child to a mixture of respiratory syncytial virus (RSV) and adenoviral infections, are scarce. In a retrospective cohort study, the study investigated the epidemiology of RSV and adenovirus infections and predictors of mixed RSV-adenoviral infections in young children hospitalized with acute lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 35 publications
2
28
0
7
Order By: Relevance
“…Most studies reported a higher frequency of respiratory viral coinfection in younger children than in older children and adults [12142728]. This presumably was caused by immature immune systems, the lack of protective immunity arising from prior exposures to viruses, and prolonged excretion of respiratory viruses in younger children compared with older children and adults [142128]. Although respiratory viral coinfection increased the rate and duration of hospitalization [141727], it eventually did not cause a poorer prognosis such as oxygen supplementation and ICU admission, compared with single viral infection [1727].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies reported a higher frequency of respiratory viral coinfection in younger children than in older children and adults [12142728]. This presumably was caused by immature immune systems, the lack of protective immunity arising from prior exposures to viruses, and prolonged excretion of respiratory viruses in younger children compared with older children and adults [142128]. Although respiratory viral coinfection increased the rate and duration of hospitalization [141727], it eventually did not cause a poorer prognosis such as oxygen supplementation and ICU admission, compared with single viral infection [1727].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even as ADV infection occurs steadily all year round in Korea, the clinical impact of respiratory viral coinfection on childhood ADV infection has rarely been reported [19]. In addition, previous studies on ADV coinfections included only children younger than 1 or 3 years of age, or children with lower respiratory tract infections [182021]. This retrospective study was performed to investigate the clinical impact of respiratory viral coinfections in Korean children with ADV infection.…”
Section: Introductionmentioning
confidence: 99%
“…En el análisis bivariado se encontró una correlación entre el número de infecciones mensuales por VSR y las variables de temperatura y precipitación (Spearman: p=0,730, p<0,01) durante el periodo de tres meses (marzo a mayo), primera época de lluvias del año en Bogotá, y evidenció un aumento en los casos positivos de VSR durante el periodo de estudio (2009 a 2011). Las otras variables no tuvieron correlación alguna con las infecciones por VSR (Rodríguez, et al, 2015).…”
Section: Estudios En Bogotáunclassified
“…Con respecto a la gravedad de la enfermedad respiratoria, 488 (21,5 %) niños fueron ingresados en la unidad de cuidados intensivos pediátricos. Del total de 2.267 pacientes incluidos en el estudio, 2.110 (93,1 %) necesitaron administración de oxígeno suplementario, 106 (4,7 %), intubación endotraqueal, 596 (26,3 %), antibióticos, y 1.008 (44,5 %), oxígeno domiciliaria; a tasa mortalidad observada fue de 1,3 % durante el periodo de estudio (Rodríguez-Martínez, et al, 2015).…”
Section: Estudios En Bogotáunclassified
See 1 more Smart Citation